A RANDOMISED CONTROL STUDY TO COMPARE THE EFFICACY OF CEFUROXIME, CLARITHROMYCIN, AND LEVOFLOXACIN IN THE MANAGEMENT OF PAEDIATRIC UPPER RESPIRATORY TRACT INFECTION - PADUGUNDLA, GOUTHAMI; V, JYOTHIRMAYEE; RAVALI, BETHALA; ARUNDHATHI, JAGILLAPURAM; SRILATHA, THAKUR; NISSI, NOORBASHA; ANJUM, ARSHIYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Background: The upper respiratory infections cause considerable morbidity mainly in children due to the fact that they mainly affect children. Accordingly, a study was conducted on antibiotics to compare the effectiveness of clarithromycin, cefuroxime, and levofloxacin for treating upper respiratory tract infections (URTI) in children. Methods: A prospective observational study for a period of 6 months was conducted in the pediatrics department of RVM hospital. Outpatients under the age of 14 years given antibiotics for the treatment of URTI were included in the study. A total of 99 study subjects were included in the study, divided into three groups each containing 33 sample sizes (clarithromycin, cefuroxime, and levofloxacin). Patient data was collected using a form and verbal consent was obtained from patients/patient representatives, and drugs were given using the lottery method. Follow-up was done and noted for the 3rd, 5th, 7th day through telephonic calls, and the collected data were evaluated using statistical analysis. Results: Pool data from 99 patients shows that many patients belong to 0–5 years age groups (age distribution), and males were more than female (gender distribution). Clarithromycin (cure rate 3 days) and cefuroxime (cure rate 5 days) showed an equal rate of cure percentage (94%), while levofloxacin for 3–5 days with a 3% failure rate. A significant difference of p<0.05 (p=0.000) was observed and no adverse events were noted. Conclusion: The study findings showed, out of 3 drugs, clarithromycin and cefuroxime showed an equal efficacy rate of 94%, but clarithromycin showed shorter duration of outcome, i.e., 3 days. Hence, clarithromycin is effective than the other two drugs in the treatment of URTI.